Evaluation and optimization of the magnetoelectric response of CoFe2O4/poly(vinylidene fluoride) composite spheres by computer simulation - Lehmann Fernández, C.S.; Pereira, N.; Lanceros-Méndez, S.; Martins, P. (Composites science and technology, 2017)
Magnetoelectric (ME) composites exhibiting strain-mediated coupling are gaining increasing interest for applications. The most interesting ones are composed of piezoelectric polymers and magnetostrictive particles. In particular, low dimensional ME materials, such as the ones in the form of micro- and nano-spheres, show strong potentials for improved energy harvesters with higher volume efficiency, sensors and actuators. Nevertheless the ME characterization of such low dimensional ME structures remain a difficult and challenging task and, therefore, the use of mathematical models and simulations are an interesting and viable option to better understand and tailor materials towards applications. In this context, the ME coupling on microspheres based on piezoelectric poly(vinylidene fluoride) (PVDF) and magnetostrictive CoFe2O4 (CFO) particles was theoretically studied based on Finite Element Methods (FEM). The effect of sphere size and filler content on the ME response was evaluated, showing that the ME response of CFO/PVDF microspheres is strongly influenced by the magnetic field intensity, sphere diameter and CFO content, being the highest ME response achieved on composite sphere with 90 wt% of CFO and 1.2 μm.